Overview of non-contributory social protection programmes in the Middle East and North Africa (MENA) region through a child and equity lens. Executive summary - Anna Carolina Machado; Charlotte Bilo; Fábio Veras Soares; Rafael Guerreiro Osorio (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
The Overview of Non-contributory Social Protection Programmes in the Middle East and North Africa (MENA) Region through a Child and Equity Lens is the first of a series of four knowledge products about non-contributory social protection in the MENA region that are being produced by a partnership between the International Policy Centre for Inclusive Growth (IPC-IG) and UNICEF Middle East and North Africa Regional Office (MENARO) (...)
Keywords: 330; Executive; Summary; Overview; Non-contributory; Social Protection; Programmes; Middle East; North; Africa; MENA; Child; Equity; Lens